Динамические параметры асинхронных двигателей частотно-регулируемых электроприводов - Акимов, Леонид Владимирович; Котляров, Владимир Олегович; Литвиненко, Дмитрий Григорьевич (НТУ "ХПИ", 2011)
В статье объединены различные обозначения физических величин, используемых для описания систем векторного и скалярного управления. Определены фактические значения динамических параметров машин на примерах серийных асинхронных двигателей

In the article, various designations of physical quantities used in scientific and technical literature for description of vector and scalar control systems are unified. Actual values of dynamic parameters of machines are defined on examples of domestic and foreign serial asynchronous motors
Dynamic parameters of variable-frequency drive asynchronous motors
Keywords: физические величины; системы управления; динамические параметры; преобразователи; asynchronous motors; scalar control; dynamic parameters